2020
DOI: 10.1111/bph.14971
|View full text |Cite
|
Sign up to set email alerts
|

Adreno–melatonin receptor complexes control ion homeostasis and intraocular pressure ‐ their disruption contributes to hypertensive glaucoma

Abstract: Background and Purpose: Often, glaucoma presents with elevated eye hydrostatic pressure, which is regulated by endogenous melatonin. Phenylephrine increases cytoplasmic [Ca 2+ ], via α 1 -adrenoceptor activation, that is detrimental in glaucoma. The aims of this study were (a) to elucidate the role of melatonin receptors in humour production and intraocular pressure (IOP) maintenance and (b) to identify glaucomarelevant melatonin-adrenoceptor interactions.Experimental Approach: Biophysical and proximity ligati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Furthermore, MT2 receptor may interact with serotonin 5-HT2C [243], being of particular interest due to the discover of agomelatine, a potent agonist of the MT1 and MT2 melatonin receptors [230] and a non-selective inhibitor of the 5-HT2C serotonin receptor [231]. Recently, interactions of MT1 and MT2 receptors with α1 antagonist have been shown to increase melatonin hypotensive effect to almost 50% and lasting for 6 h [244].…”
Section: Melatonin and Analogs: Its Function On Iopmentioning
confidence: 99%
“…Furthermore, MT2 receptor may interact with serotonin 5-HT2C [243], being of particular interest due to the discover of agomelatine, a potent agonist of the MT1 and MT2 melatonin receptors [230] and a non-selective inhibitor of the 5-HT2C serotonin receptor [231]. Recently, interactions of MT1 and MT2 receptors with α1 antagonist have been shown to increase melatonin hypotensive effect to almost 50% and lasting for 6 h [244].…”
Section: Melatonin and Analogs: Its Function On Iopmentioning
confidence: 99%
“…Once again, the heteromeric context leads to a change, from G q to G s , in the G protein coupling (see Figure 1 bottom). Glaucoma coursing with elevated intraocular pressure is correlated with a decreased expression of the complexes in stromal cells (Alkozi et al, 2019;Alkozi et al, 2020). Whether this fact is a cause or a consequence of the disease, the melatoninadrenergic heteromers arise as targets for fighting the disease.…”
Section: The Alternative Mechanism To Approach Biased Signaling How the Endogenous Agonist May Provide Functional Diversitymentioning
confidence: 99%
“…Crooke et al (2013) confirmed in vitro the indirect action of melatoninergic compounds on adrenergic receptors and their remarkable effect upon the ocular hypotensive action in rabbits mainly of alpha-2 adrenergic receptor agonists but also of beta-adrenergic antagonists. More recently, Alkozi et al (2020) demonstrated that α-adrenergic and melatonin receptors form functional complexes in which the C-terminal tail of the adrenergic receptor play a relevant role, identifying that the number of complexes significantly decreased in models of glaucoma and, more importantly, in human samples of glaucoma patients. Remarkably, coinstillation of melatonin resulted in long-term decreases in the intraocular pressure in a well-established animal model of glaucoma, hypothesizing that melatonin could normalize pressure in glaucoma (Alkozi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Alkozi et al (2020) demonstrated that α-adrenergic and melatonin receptors form functional complexes in which the C-terminal tail of the adrenergic receptor play a relevant role, identifying that the number of complexes significantly decreased in models of glaucoma and, more importantly, in human samples of glaucoma patients. Remarkably, coinstillation of melatonin resulted in long-term decreases in the intraocular pressure in a well-established animal model of glaucoma, hypothesizing that melatonin could normalize pressure in glaucoma (Alkozi et al, 2020). These findings are crucial to understand the potential physiological functions and implications of the melatonin supplementation to address pathological dysfunctions by targeting distinct receptors and their complexes.…”
Section: Discussionmentioning
confidence: 99%